2022
DOI: 10.1038/s41598-021-04252-1
|View full text |Cite
|
Sign up to set email alerts
|

New tip-apex distance and calcar-referenced tip-apex distance cut-offs may be the best predictors for cut-out risk after intramedullary fixation of proximal femur fractures

Gaetano Caruso,
Nicola Corradi,
Antonio Caldaria
et al.

Abstract: Cut-out is one of the most common mechanical failures in the internal fixation of trochanteric hip fractures. The tip-apex distance (TAD), and the calcar-referenced tip apex distance (CalTAD) are the radiographic parameters that most predict the risk of cut-out. The optimal CalTAD value has not yet been defined, but the optimal TAD value is reported as 25 mm or less. However, this cut-off is highly specific but poorly sensitive. The aim of this study was to determine highly specific and sensitive TAD and CalTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
14
1
3
Order By: Relevance
“…Moreover, the correlation between TAD and fixation failure was not proven in our findings. In general, a TAD <25mm is recommended to lessen the risk of fixation failure in intramedullary hip nails, although evidence for this is limited [13] and several authors have reported that longer TAD and calcar-referenced tip-apex distance (CalTAD) do not, in fact, increase cutout risk [14]. In our study, 29% of patients had a TAD >25 mm, and yet none of them presented a mechanical failure.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, the correlation between TAD and fixation failure was not proven in our findings. In general, a TAD <25mm is recommended to lessen the risk of fixation failure in intramedullary hip nails, although evidence for this is limited [13] and several authors have reported that longer TAD and calcar-referenced tip-apex distance (CalTAD) do not, in fact, increase cutout risk [14]. In our study, 29% of patients had a TAD >25 mm, and yet none of them presented a mechanical failure.…”
Section: Discussionmentioning
confidence: 54%
“…Particular attention should be paid to fracture site reduction and lag screw positioning to diminish mechanical complications such as lag screw cut-out, which aggravate morbidity and mortality associated with proximal femur fractures [ 4 ]. Studies have provided the first clinical evidence bolstering the validity and reliability of CalTAD as a predictor of lag screw cut-out, which is a measurement method that favors the inferior–central region of the femoral head for placing the lag screw [ 4 , 5 ]. The value of CalTAD appears to be more effectual than the TAD value in predicting the risk of the cut-out in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The value of CalTAD appears to be more effectual than the TAD value in predicting the risk of the cut-out in the postoperative period. However, the discrepancy between the two methods is minimal [ 5 ]. In addition, searching the existing literature, no studies demonstrate greater sensitivity and specificity of CalTAD than TAD and vice-versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Cutting-out of the lag screw is the main complication of proximal femur fracture fixation. 12 The strongest predictor of cutting-out in femoral nailing is tip-apex distance (TAD). 13 Distances less than 25 mm are associated with a significantly decreased risk of slippage of the cephalic screw, 14 while there is a very strong statistical relationship between a TAD greater than 25 mm and mobilization of the cephalic screw.…”
Section: Introductionmentioning
confidence: 99%